Fat Graft Myringoplasty- Day Care Procedure: Role in Small Central Perforations - Manpreet Singh Nanda; Mandeep Kaur; Dinesh Luthra (International Journal of Medical Research and Review, 2015)
Introduction: Day care surgery is the need of hour in the field of otology. Temporalis fascia is the most common material used for closure of tympanic membrane perforation. But it is a lengthy procedure requiring general anaesthesia (GA) or longer sedation, extensive middle ear manipulation and a longer recovery post operatively. Fat is said to have angiogenetic properties. The aim of this study is to evaluate the usefulness of adipose tissue fat for closure of dry small perforations of tympanic membrane as a day care procedure.Materials and Methods: 40 patients with small central dry tympanic membrane perforations were taken up for surgery under sedation using fat graft from ear lobule for closure of perforations. The results were evaluated inta operatively, immediate post operatively and at 1st, 4th , 8th and 12th monthly post operative visit for uptake of graft, hearing improvement and complications of the procedure if any.Results: The results showed that the graft uptake success rate`was high as good as traditional myringoplasty using temporalis fascia. The procedure was minimally invasive, requiring little sedation, taking much less time, cost effective where both ears can be operated in the same sitting and the patients can be discharged on the same day with no major complications. There was considerable hearing improvement noted in the patients in the study.Conclusion: So it can be concluded that fat graft myringoplasty is an effective method for closure of small central dry tympanic membrane perforations.